Pendampingan Legalitas PIRT Pada UMKM Hasil Olahan Laut Di Desa Padelegan Kecamatan Pademawu Kabupaten Pamekasan - Dewi Mutiah; Aprilina Pawestri; Ansori Ansori (Lembaga Pengembangan Kinerja Dosen, 2024)
Padelegan village is a village that has a variety of processed seafood. Padelegan village has several MSMEs managed by the des aitu community itself. MSME products produced are in the form of processed marine products. Such as anchovy krispi, crab crackers, rengginang lorjuk, and others. The problem experienced by MSMEs in Padelegan Village is that they do not have a PIRT permit which has an impact on product distribution. The solution to this problem is the existence of Pirt permits which will have an impact on product distribution because consumer confidence increases. Community service activities through the Independent Community Service grant program aim to assist MSME actors in applying for Pirt permits. The method of community service consists of several stages, namely preparation, discussion, implementation and assistance, monitoring and evaluation. The method used in this service is to provide assistance in the management of household industrial production certificate (PIRT). The results of this service activity are in the form of Pirt permits owned by partners